(untitled) (KIUT Publication, 2025)
Modern medical education, in the context of rapidly advancing technologies, requires new approaches. Digitalization and artificial intelligence (AI) technologies play a crucial role in effectively acquiring medical knowledge and practical skills. In particular, the use of AI tools in simulation-based training provides students with the opportunity to practice in a realistic, safe, and interactive environment. This, in turn, enhances their clinical reasoning, problem-solving, and decision-making skills.